2019
DOI: 10.11648/j.wjfst.20190301.13
|View full text |Cite
|
Sign up to set email alerts
|

Comparative of Proximate and Mineral Composition of Commercially-Available Millet Types in Katsina Metropolis, Nigeria

Abstract: The study revealed a high nutritional quality and possible therapeutic effect of the studied millet varieties which are locally sourced and relatively cheaper source of food for a teeming population like ours. The millet varieties were obtained from the central market in Katsina state, Nigeria. The millet varieties (finger millet, pearl millet and fonio millet) were cleaned by washing in water, de-watered, sun dried, milled into flour and stored in sealed polythene bags. The results obtained from the studied m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 8 publications
0
0
2
Order By: Relevance
“…Potassium on the other hand, was the amplest mineral in the current study, the types used however, contain less than what was reported by Mariod et al (2017) but more than Abdulrahmani and Omoniyi (2016) who reported the value of 366.67 mg/100 g in millet types. Manganese content was higher in the finger millet types; the result is higher than the values reported by Sanusi et al (2019). The iron content of the current study was also reported to be higher than 1.25 to 1.46 as indicated by Sanusi et al (2019).…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Potassium on the other hand, was the amplest mineral in the current study, the types used however, contain less than what was reported by Mariod et al (2017) but more than Abdulrahmani and Omoniyi (2016) who reported the value of 366.67 mg/100 g in millet types. Manganese content was higher in the finger millet types; the result is higher than the values reported by Sanusi et al (2019). The iron content of the current study was also reported to be higher than 1.25 to 1.46 as indicated by Sanusi et al (2019).…”
Section: Discussioncontrasting
confidence: 57%
“…Manganese content was higher in the finger millet types; the result is higher than the values reported by Sanusi et al (2019). The iron content of the current study was also reported to be higher than 1.25 to 1.46 as indicated by Sanusi et al (2019).…”
Section: Discussioncontrasting
confidence: 57%